THE SUPERVISED CURRICULAR TRAINING AS FIELD KNOWLEDGE: CONCEPTIONS AND RESEARCH TRENDS (Fiep Bulletin - online, 2011)
The research characterizes a bibliographical study that has as objective to argue aspects related to the supervised curricular training. It dialogues with studies that relate it to the field of knowledge and analyzes investigative conceptions and trends in this context. It concludes that for the training to leverage a solid background not only of teachers-students but also students of other teachers, it needs to be anchored on a project to promote reflection on teaching activity and the training as part of teacher training, it can point meaningful learning, since that it has as reference the school in its possibilities and limitations, though without ignoring the exchange of experience and participation of all (pairs of school and university).
Keywords: training; future teachers; school